Brace technology thematic series: the progressive action short brace (PASB) - Aulisa, Angelo G (BioMed Central, 2012)
BACKGROUND: The Progressive Action Short Brace (PASB) is a custom-made thoraco-lumbar-sacral orthosis (TLSO), devised in 1976 by Dr. Lorenzo Aulisa (Institute of Orthopedics at the Catholic University of the Sacred Heart, Rome, Italy). The PASB was designed to overcome the limits imposed by the trunk anatomy. Indeed, the particular geometry of the brace is able to generate internal forces that modify the elastic reaction of the spine. The PASB is indicated for the conservative treatment of lumbar and thoraco-lumbar scoliosis. The aim of this article is to explain the biomechanic principles of the PASB and the rationale underlying its design. Recently published studies reporting the results of PASB-based treatment of adolescent scoliotic patients are also discussed. DESCRIPTION AND PRINCIPLES: On the coronal plane, the upper margin of the PASB, at the side of the curve concavity, prevents the homolateral bending of the scoliotic curve. The opposite upper margin ends just beneath the apical vertebra. The principle underlying such configuration is that the deflection of the inferior tract of a curved elastic structure, fixed at the bottom end, causes straightening of its upper tract. Therefore, whenever the patient bends towards the convexity of the scoliotic curve, the spine is deflected. On the sagittal plane, the inferior margins of the PASB reach the pelvitrochanteric region, in order to stabilize the brace on the pelvis. The transverse section of the brace above the pelvic grip consists of asymmetrical ellipses. This allows the spine to rotate towards the concave side only, leading to the continuous generation of derotating moments. On the sagittal plane, the brace is contoured so as to reduce the lumbar lordosis. The PASB, by allowing only those movements counteracting the progression of the curve, is able to produce corrective forces that are not dissipated. Therefore, the brace is based on the principle that a constrained spine dynamics can achieve the correction of a curve by inverting the abnormal load distribution during skeletal growth. RESULTS: Since its introduction in 1976, several studies have been published supporting the validity of the biomechanical principles to which the brace is inspired. In this article, we present the outcome of a case series comprising 110 patients with lumbar and thoraco-lumbar curves treated with PASB brace. Antero-posterior radiographs were used to estimate the curve magnitude (C(M)) and the torsion of the apical vertebra (T(A)) at 5 time points: beginning of treatment (t(1)), one year after the beginning of treatment (t(2)), intermediate time between t(1 )and t(4 )(t(3)), end of weaning (t(4)), 2-year minimum follow-up from t(4 )(t(5)). The average C(M )value was 29.3°Cobb at t(1 )and 13.0°Cobb at t(5). T(A )was 15.8° Perdroille at t(1 )and 5.0° Perdriolle at t(5). These results support the efficacy of the PASB in the management of scoliotic patients with lumbar and thoraco-lumbar curves. CONCLUSION: The results obtained in patients treated with the PASB confirm the validity of our original biomechanical approach. The efficacy of the PASB derives not only from its unique biomechanical features but also from the simplicity of its design, construction and management.